The impact of prolonged, maternal iodine exposure in early gestation on neonatal thyroid function - Mathews, Divya M.; Peart, Jane M.; Sim, Robert G.; O’Sullivan, Susannah; Derraik, José G. B.; Heather, Natasha L.; Webster, Dianne; Johnson, Neil P.; Hofman, Paul L. (Frontiers in Endocrinology, 2023)
Context: Hysterosalpingography (HSG) using oil-soluble contrast medium (OSCM) improves pregnancy rates but results in severe and persistent iodine excess, potentially impacting the fetus and neonate. Objective: To determine the incidence of thyroid dysfunction in newborns conceived within six months of OSCM HSG. Design: Offspring study of a prospective cohort of women who underwent OSCM HSG. Setting: Auckland region, New Zealand (2020-2022) Participants: Offspring from the SELFI (Safety and Efficacy of Lipiodol in Fertility Investigations) study cohort (n=57). Measurements: All newborns had a dried blood spot card for TSH measurement after 48 hours of birth as part of newborn screening. Forty-one neonates also had a heel prick serum sample at one week for thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3). Maternal urine iodine concentration (UIC) and TSH in the six months after OSCM HSG were retrieved from the SELFI study for analyses. Primary outcome: Incidence of hypothyroidism in the neonatal period. Results: There was no evidence of primary hypothyroidism on newborn screening (TSH 2-10 mIU/L). All neonates tested at one week had normal serum TSH, FT4 and FT3 levels. However, increasing maternal peak UIC levels during pregnancy were associated with lower TSH levels (p= 0.006), although also associated with lower FT4 levels (p=0.032). Conclusions: While pre-conceptional OSCM HSG in women did not result in neonatal hypothyroidism, gestational iodine excess was associated with a paradoxical lowering of neonatal TSH levels despite lower FT4 levels. These changes likely reflect alterations in deiodinase activity in the fetal hypothalamic-pituitary axis from iodine excess. Trial registration: This study is registered with the Australian New Zealand Clinical Trials Registry (ANZCTR: 12620000738921); https://anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12620000738921.